Issues in Curriculum and Pedagogical Practices in Madarsa under Modernisation Programme - KAYOOM, HUMA (JOURNAL OF INDIAN EDUCATION, 2025)
Before the arrival of colonial education, madarsa system of education along with the indigenous system of education flourished well in India. However, the repercussion of the revolt of 1857 gave a serious setback to madarsa education. After India gained independence the secular nature of the state led to the establishment of secular system of education in India. Though Muslims can access the secular schools as well, sometimes madarsas can be the only educational option available to muslim children especially those belonging to the marginalised community. Many of the previous researchers pertaining to the review of muslim education in India have highlighted the fact that the children of the educationally backward muslim community attend maktabs, madarsas and darul-ulooms with very little participation in the national mainstream education system. These religious institutions to a larger extent provide religious teaching. In order to provide them access to education in modern subjects, the Union Government has been implementing the scheme of even Madarsa Modernisation Programme (MMP) since the 1990s. Unfortunately, even after such a long time, madarsa graduates cannot compete with the students of mainstream education (with a few exceptions). This investigative paper tends to explore those curricular issues and pedagogical practices, which are prevalent in madarsa education that create hurdle in the educational development of the students studying in these madarsas. For the study of the pedagogical practices inside madrasa, the researcher conducted classroom observations in one of the Government-aided madarsa in Varanasi city registered under Madarsa Modernisation Programme and to study the issues in curriculum of madarsas, content analysis of the curriculum framework of Uttar Pradesh Madarsa Board of Education in the light of National Curriculum Framework (NCF) 2005 has been done.